Retinoblastoma susceptibility gene product pRB activates hypoxia-inducible factor-1 (HIF-1) - Budde, Andreja; Petersen, Gabriele (Oncogene, 2005)
Hypoxia-inducible factor-1 alpha (HIF-1) constitutes a regulatory subunit of HIF-1, a major transcriptional activator of genes that coordinate physiological and pathological responses towards hypoxia. In order to identify novel interaction partners of HIF-1 we have applied T7 phage display system and identified a domain inherent in the retinoblastoma protein (pRB). The interaction between pRB and HIF-1 was confirmed by in vitro experiments and in transfected cells. Thereby, an HIF-1 domain spanning amino acids 530-694 was mapped to be required for pRB binding. Overexpression of pRB provoked transcriptional activation of HIF-1 under normoxia. Furthermore, the domain of pRB identified to bind HIF-1 in vitro is sufficient to cause HIF-1 transcriptional activation with the further notion that phosphorylation deficient pRB shows stronger HIF-1 transactivation. Using ChIP analysis, we show that HIF-1 responsive elements (HREs) are precipitated using -pRB antibodies. Additionally, a functional interaction between pRB and HIF-1 is confirmed by showing that HIF-1 reverses the transcription repressor function of pRB.
Gesehen am 24.05.2017